Monetary Policy at Work: Security and Credit Application Registers Evidence - José-Luis Peydró; Andrea Polo; Enrico Sette (ZBW – Leibniz Information Centre for Economics, 2020)
Monetary policy transmission may be impaired if banks rebalance their portfolios towards securities to e.g. risk-shift or hoard liquidity. We identify the bank lending and risk-taking channels by exploiting – Italian's unique – credit and security registers. In crisis times, with higher ECB liquidity, less capitalized banks react by increasing securities over credit supply, inducing worse firm-level real effects. However, they buy securities with lower yields and haircuts, thus reaching-for-safety and liquidity. Differently, in pre-crisis time, securities do not crowd-out credit supply. The substitution from lending to securities in crisis times helps less capitalized banks to repair their balance-sheets and then restart credit supply with a one year-lag.
Keywords: G01; G21; G28; E52; E58; 330; securities; credit supply; bank capital; monetary policy; reach-for-yield; haircuts; held to maturity; available for sale; trading book; Euro Area Sovereign Debt Crisis